2002
DOI: 10.2117/psysoc.2002.250
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Performance in Context: The Influence of Goal Orientations and Instructional Setting on Situational Appraisals and Task Performance

Abstract: The purpose of this study was to examine how students with different goal orientation patterns perform in a complex problem solving task under different instructional conditions. Ninth-grade students (N=143) performed a complex problem solving task after receiving either task-involving or ego-involving instructions. It was assumed that students emphasizing performance and avoidance goals (or both) would produce less positive situational appraisals than students emphasizing learning goals, and that these differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(139 citation statements)
references
References 80 publications
6
117
0
16
Order By: Relevance
“…Multiple goals perspective (Pintrich, 2000) states that students could pursue multiple orientations or have different reasons in achieving a particular outcome (Niemivirta, 2002;Pastor, Barron, Miller, & Davis, 2007;Pintrich, 2000;Tumoninem-Soini et al, 2008;Tuominem-Soini, Salmela-Aro, & Niemivirta, 2011). Several studies found multiple motivational profiles in elementary, middle school and high school students and, although differing in the number of clusters and in its labels (Daniels, Haynes, Stupnisky, Perry, Newall, & Pekrun, 2008;Luo, Paris, Hogan, & Luo, 2011;Niemivirta;2002;Tuominem-Soini et al, 2008, 2012, students tended to manifest more adaptive profiles when combining both high task orientation and high selfenhancing orientation (Daniels et al, 2008;Niemivirta, 2002;Pintrich, 2000;Tumoninem-Soini et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple goals perspective (Pintrich, 2000) states that students could pursue multiple orientations or have different reasons in achieving a particular outcome (Niemivirta, 2002;Pastor, Barron, Miller, & Davis, 2007;Pintrich, 2000;Tumoninem-Soini et al, 2008;Tuominem-Soini, Salmela-Aro, & Niemivirta, 2011). Several studies found multiple motivational profiles in elementary, middle school and high school students and, although differing in the number of clusters and in its labels (Daniels, Haynes, Stupnisky, Perry, Newall, & Pekrun, 2008;Luo, Paris, Hogan, & Luo, 2011;Niemivirta;2002;Tuominem-Soini et al, 2008, 2012, students tended to manifest more adaptive profiles when combining both high task orientation and high selfenhancing orientation (Daniels et al, 2008;Niemivirta, 2002;Pintrich, 2000;Tumoninem-Soini et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found multiple motivational profiles in elementary, middle school and high school students and, although differing in the number of clusters and in its labels (Daniels, Haynes, Stupnisky, Perry, Newall, & Pekrun, 2008;Luo, Paris, Hogan, & Luo, 2011;Niemivirta;2002;Tuominem-Soini et al, 2008, 2012, students tended to manifest more adaptive profiles when combining both high task orientation and high selfenhancing orientation (Daniels et al, 2008;Niemivirta, 2002;Pintrich, 2000;Tumoninem-Soini et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, personality factors may have a great impact on this matter. From the perspective of personality, interest should depend on both a problem-solver's ability as well as on habitual preferences for difficult or simple ventures as related to achievement motivation [30]. In this case, however, indirect indicators of ability (school grades) turned out to be non-predictive.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conceptualized the multiplicity of goals in terms of different achievement-related orientations that may or may not occur in combination. Young people could, for instance, be motivated to acquire new knowledge and/or to do better than others and/or to put forth as little effort as possible when striving for academic goals (see Niemivirta, 2002). Flunger and her colleagues argued that these multiple orientations have meaningful associations with the 276 TOMASIK youth' identity development status and with various aspects of goal striving such as commitment, effort, and progress.…”
Section: Current Research On Multiple Goalsmentioning
confidence: 99%